Rethinking ethnic migrant health research: creating space for diverse paradigms - Rachel Mukwezwa Tapera (Kōtuitui)
Health research often does not reflect the diversity of worldviews and knowingness inherent in Aotearoa New Zealand (NZ). Eurocentric paradigms – grounded in individualism, empirical rationalism, objectivity, neutrality, and the universality of theories – continue to dominate. Despite efforts to produce culturally safe research and healthcare practice in Aotearoa NZ, diverse and inclusive paradigms and epistemologies are less visible. This paper argues for holistic approaches to research founded in diverse paradigms to understand the complex issues that underpin the health of ethnic migrant communities (EMCs) and interrogate the status quo of health research and practice in Aotearoa NZ more fundamentally. This paper examines alternative epistemologies that are relevant to extend beyond the current conceptualisation of the healthy migrant effect. By exploring diverse paradigms, we aim to enhance our understanding of ethnic migrant health in Aotearoa NZ. The paper also presents frameworks that support diverse paradigms and some guiding tenets drawn from the collective values of EMCs that may apply to reorienting ethnic migrant health research and care in Aotearoa NZ.